Learning by Herding – Transmission of Sámi Reindeer Herding Knowledge and Skills - Bongo, Mathis Persen; Eira, Inger Marie Gaup (Springer International Publishing, 2022)
Abstract The chapter addresses the issues of disseminating the knowledge and skills of the Sámi reindeer herders: frameworks, methodologies, and ways of knowledge transmission in reindeer husbandry. The chapter overviews existing teaching practices, learning levels, and learning arenas, comparing traditional knowledge transmission and academic curriculum. The authors discuss lifelong learning, systematic learning methods, and responsibilities. The chapter findings are based on the interviews with the Sámi reindeer herders from Guovdageaidnu/Kautokeino, a literature review, and author’s reindeer herding experiences.